Pesticide spraying robot for precision agriculture: A categorical literature review and future trends - Meshram, Ashish T.; Vanalkar, Anil V.; Kalambe, Kavita B.; Badar, Avinash M. (Journal of field robotics, 2022)
Pesticide spraying is one of the risky and very essential task in agriculture to protect plants from harmful organisms. Many farmers are used manual pesticide spraying devices that they carry these devices on their shoulders and spray on the entire plant. Due to this, harmful pesticide chemicals spread into the air and may enter into the body of farmers and farm workers through the breathing system and mostly affect their body parts even, so many farmers lost their life. For this serious problem, we present the best solution to perform this task without the intervention of man is to utilize a robotic system in an agriculture. This paper analyses the state‐of‐the‐art reviews in the development of autonomous pesticide spraying robots that are divided into four main categories; platform mobility and steering, localization and navigation control, sensing and target detection, and pesticide spraying arrangement. This paper also focused on the efficient methodology that can be used for future perspectives to enhance pesticide spraying operations in an agriculture. In this paper, to achieve target spraying operation, a suitable navigation control algorithm for platform movement and an efficient trajectory planning algorithm for shortest link movement are designed which covers the shortest distance to visit all targeted pests on the plant. This technique will help to reduce the overdose of toxic pesticides hence minimize the wastage of pesticides and also control its dangerous effects on the human being and on the environment.